Rapid and Reliable HPLC Method for the Simultaneous Determination of Dihydroxyacetone, Methylglyoxal and 5-Hydroxymethylfurfural in Leptospermum Honeys. - Matthew Pappalardo; Linda Pappalardo; Peter Brooks (PLoS ONE, 2016)
A reliable determination of dihydroxyacetone, methylglyoxal and 5-hydroxymethylfurfural is essential to establishing the commercial value and antimicrobial potential of honeys derived from the Leptospermum species endemic to Australia and New Zealand. We report a robust method for quantitation of all three compounds in a single HPLC run. Honey samples (n = 6) that are derivatized with o-(2,3,4,5,6-Pentafluorobenzyl) hydroxylamine were quantitated against a stable anisole internal standard. Linear regression analysis was performed using calibration standards for each compound (n = 6) and results indicated a high degree of accuracy (R2 = 0.999) for this method. The reliability of some commercial methylglyoxal solutions were found to be questionable. Effective quantitation of methylglyoxal content in honey is critical for researchers and industry, and the use of some commercial standards may bias data. Two accurate methylglyoxal standards are proposed, including a commercial standard and a derivative that can be prepared within the laboratory.